Perda Syariah di Serambi Madinah: Studi Atas Perda No 6/2012 tentang Kewajiban Baca Tulis Al-Qur’an di Kota Gorontalo - Korompot, Wahyudi; Fata, Ahmad Khoirul; Santoso, Eka Putra B.; Kango, Andries (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2024)
Quranic education has long been a deeply ingrained tradition in Gorontalo City, often referred to as the "Veranda of Madinah." The enactment of Local Regulation Number 6 of 2012 on the Mandatory Reading and Writing of the Al-Quran in Gorontalo City can be seen as a form of state accommodation of this local wisdom. This study examines the background, legalization process, and implementation of Local Regulation Number 6 of 2012 among the people of Gorontalo City. Employing a qualitative descriptive research method based on George C. Edward's theory, the study finds that the implementation of Local Regulation Number 6 of 2012 was only active and had programs for two years during the leadership of Adhan Dambea. After Adhan Dambea's term ended, no further programs were implemented by the government related to the Local Regulation. However, Quranic education remains widespread in Gorontalo City. In reality, the people of Gorontalo provide Quranic education not based on their knowledge of Local Regulation Number 6 of 2012, but rather out of their own self-awareness as Muslims, a tradition deeply embedded in their society.